2018
DOI: 10.1177/0265659018755525
|View full text |Cite
|
Sign up to set email alerts
|

Facilitated playgroups to promote speech and language skills of young children with communication delays: A pilot study

Abstract: Family-centered practices that build caregiver capacity are a central focus of early intervention services for young children with disabilities. The purpose of this study was to evaluate the feasibility of adapting the 'Parents Interacting with Infants' (PIWI) facilitated playgroup model to target effective communication strategies for parents of young children with communication delays. A concurrent multiple baseline across behaviors design with three parent-child dyads was used to determine the effects of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
0
6
0
3
Order By: Relevance
“…Other researchers estimated that intelligent tutoring systems were developed to help students learn independently. However, students, who are weak selfregulated learners, often struggle with using these systems because they lack the necessary skills to learn independently (Green et al, 2018;Zare & Zade, 2014). They further found that the feasibility of using a facilitated playgroup model could enhance parents" ability to implement effective communication strategies for their children.…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers estimated that intelligent tutoring systems were developed to help students learn independently. However, students, who are weak selfregulated learners, often struggle with using these systems because they lack the necessary skills to learn independently (Green et al, 2018;Zare & Zade, 2014). They further found that the feasibility of using a facilitated playgroup model could enhance parents" ability to implement effective communication strategies for their children.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of attending a supported playgroup, young mothers formed an understanding of their child's developmental needs, which was perceived as an enabler to access. Supported playgroups are shown to have an important role in facilitating a mother's understanding of child developmental milestones and connecting mothers to health services that are specific to their child's needs (Green, Towson, Head, Janowski, & Smith, 2018). This enabler is best modified through reinforcement, optimism, and beliefs about capabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Il serait également pertinent de documenter les stratégies utilisées pour faciliter les interactions de l'enfant, que ce soit l'enseignement aux proches de l'enfant ("coaching") le soutien apporté aux éducatrices en milieu de garde ainsi que les modifications apportées dans l'environnement (Schuele et al 1995;Snyder et al 2015). Si ces techniques sont une pratique clinique de plus en plus fréquente et que l'efficacité de plusieurs modèles utilisant le "coaching" aux parents ou aux éducatrices a été documentée dans la littérature scientifique (Green et al 2018;Frantz et al 2019;Weitzman et al 2017)…”
Section: Discussionunclassified
“…D'une part, des stratégies utilisées en modalité individuelle, comme les explications directes, l'utilisation d'un soutien visuel ou la mise en pratique des habiletés enseignées, sont mises à profit pour cibler la communication en contexte groupe (Gerber et al 2012;Snyder et al 2015). D'autre part, certaines stratégies visent à modifier le contexte d'interaction dans lequel les habiletés sociales sont réalisées, par exemple le coaching aux parents et à l'entourage de l'enfant, le modèle par les pairs et la modification de l'environnement d'apprentissage (Green et al 2018;Milam et al 2020;Schuele et al 1995;Snyder et al 2015).…”
Section: L'intervention Pragmatique Chez Les Enfants Ayant Un Tdlunclassified
See 1 more Smart Citation